CACNA1A Gene Variants in Eight Chinese Patients With a Wide Range of Phenotypes - Zhang, Linxia; Wen, Yongxin; Zhang, Qingping; Chen, Yan; Wang, Jiaping; Shi, Kaili; Du, Lijun; Bao, Xinhua (Frontiers in Pediatrics, 2020)
Background: CACNA1A gene encodes the voltage-dependent P/Q-type calcium channel subunit alpha-1A, which is widely expressed throughout the CNS. The biological roles of P/Q channel are diverse and the phenotypic spectrum caused by CACNA1A mutations is wide. The aim of this study is to demonstrate its phenotypic diversity and analyze the genotype-phenotype correlations in a cohort of Chinese patients. Methods: Patients with hemiplegic migraine, cerebellar ataxia, developmental delay or epilepsy without known causes were tested by trios whole-exome sequencing. Patients with pathogenic CACNA1A gene variants were recruited. The clinical information of the patients was collected, and the association between the genotype and the phenotype was investigated. Results: Totally, 8 patients, 6 females and 2 males were found to have CACNA1A gene variants. All the variants were de novo including 6 missense variants and 1 frameshift variant. Four de novo missense variants found in 5 patients located in the S4, S5 or S6 transmembrane segments of Domain II and III (p.R1352Q, p.G701V, p.A713T, p.V1393M). All of them were correlated with severe phenotypes, including 3 sporadic hemiplegic migraine type 1 and epilepsy, 2 developmental and epileptic encephalopathy. The other 2 missense variants, p.Y62C and p.F1814L, located in the cytoplasmic side of N-terminus and C-terminus respectively. The variant p.Y62C was associated with severe Hemiconvulsion-Hemiplegia-Epilepsy syndrome, and p.F1814L was associated with relatively mild phenotype. All the missense variants were speculated as gain-of-function (GOF) mutations. The only frameshift variant, p.Q681Rfs*100, a lose-of-function (LOF) mutation, was found in a patient with episodic ataxia type 2. Meanwhile, all the patients had developmental delay ranged from mild to severe, as well as cerebellar ataxia including 1 congenital ataxia, 1 episodic ataxia, and 6 non-progressive ataxia. Conclusions: CACNA1A variants could lead to a wide spectrum of neurological disorders including epileptic or non-epileptic paroxysmal events, cerebellar ataxia and developmental delay. The variants could be both GOF mutation and LOF mutation. There appeared to be some correlations between genotype and phenotype.